Evaluation of “Open Essence” odor-identification test card by application to healthy volunteers - Okutani, Fumino; Hirose, Kahori; Kobayashi, Taisuke; Kaba, Hideto; Hyodo, Masamitsu (Auris, nasus, larynx, 2013)
In the United States and European countries, the University of Pennsylvania Smell Identification Test (UPSIT), the Quick Smell Identification Test (Q-SIT), a shorter version of the UPSIT, and “Sniffin’ Sticks” are widely used for testing olfaction. The odor stick identification test for Japanese (OSIT-J) has been manufactured in Japan. This was followed by the development of “Open Essence,” consisting of cards that make use of sealed odorants. This study examined the usefulness of Open Essence in young volunteers with normal olfaction. The participants were 176 medical students in their clinical clerkships at the Department of Otolaryngology, Kochi Medical School Hospital. There were 111 males and 65 females, with a median age of 24 years (range 22–42 years). The olfactory function of all participants was confirmed as normal by screening with T&T olfactometry. Before beginning Open Essence, the subjects were asked to answer a questionnaire on their olfaction and habits. Females had significantly better smell identification than males. Of the 12 odorants, “perfume” and “cooking gas” were difficult to identify, because perfume involves different imagery and the compounds that give the smell of gas are readily volatilized. In contrast, all participants recognized “curry” and “menthol,” probably because they are received as both somatosensory stimuli and smell. These results suggest that, with improvement, Open Essence might be used for testing olfaction in Japanese subjects.